Improving Pupils’ Religious Literacy Through The Reading Corner Programme at MI Matalibul Huda Mlonggo - Muhammad Zufa Chilmi Asyam; Ana Rahmawati (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2026)
Religious literacy is an important competency in madrasah ibtidaiyah (elementary Islamic school) education, especially in text-based religious subjects. However, the religious literacy skills of MI students are still relatively low, as indicated by their lack of interest in reading and difficulty in understanding religious texts. This study aims to examine the implementation of the reading corner programme and its role in improving the religious literacy of students at Matholibul Huda Mlonggo MI. The research used a qualitative approach with an in-depth case study through observation, in-depth interviews, and documentation, as well as data analysis using the Miles, Huberman, and Saldaña model. The results showed that the reading corner programme was implemented continuously with the support of facilities, teachers, and madrasah policies, and was utilised as part of learning through regular reading habits. This programme contributed positively to improving students' religious understanding, especially through narrative and visual readings, although the improvement was not yet evenly distributed among all students. Therefore, a variety of reading materials and teacher assistance are needed to optimise the improvement of students' religious literacy.